Introns of the chicken ovalbumin gene promote nucleosome alignment in vitro. - Lauderdale, J D (1992)
A defined in vitro chromatin assembly system was used to examine the nucleosome alignment induced by histone H5 throughout a 12 kilobase pair chicken genomic DNA fragment containing the ovalbumin gene. In contrast with total fragmented chicken DNA and several anonymous cloned fragments, much of the gene permitted histone H5 to space nucleosomes at physiological intervals in an extended array. Nucleosomes at the 3'-end of the gene and on approximately 4 kilobase pairs of 5'-flanking ovalbumin sequence did not become aligned to appreciable extents. Analysis of cloned 2-3 kilobase pair subfragments suggested that a strong nucleosome alignment signal, specifying a 196 +/- 5 base pair repeat exists in intron E. A second discrete region of the gene, which mapped approximately to intron A, exhibited nucleosome alignment with a spacing periodicity of about 200 base pairs. The ovalbumin cDNA did not permit nucleosome alignment. These findings suggest that some of the introns contain signals that direct nucleosome alignment over the ovalbumin gene in a way conducive to its regulation.